Recreational sport program design, delivery, and management - Barcelona, Robert J. 1970-; Wells, Mary Sara; Arthur-Banning, Skye (Human Kinetics, 2016)
There are more opportunities than ever for employment in recreational sport, which means the need to prepare students with a solid foundation of the design, delivery, and management of recreational sport has never been more critical. Recreational Sport is designed precisely with that need in mind. This text provides a contemporary perspective of recreational sport management, offering a comprehensive picture of recreational sport management for people in or entering all sectors of recreation and leisure, including public, nonprofit, private, and commercial. Barcelona and his coauthors help readers gain those skills in part by simplifying the complicated process of designing and delivering programs in various settings in recreation and leisure services. They present a macrocosm view of recreational sport in communities--a view that reflects the most current, application-based research in the field. Their text places recreational sport squarely in the middle of the recreation and leisure curriculum and is supported by the recreational sport core competencies as developed by Barcelona himself. Those competencies are based on what recreational sport managers need to know and be able to do to grow and succeed in the profession, and they connect with the NIRSA recreational sport competencies developed in 2013. -- Publisher's website